CYP19 gene polymorphism as the potential risk factor of endometrial cancer - Kulig, Bartosz; Przybyłowska, Karolina; Smolarz, Beata; Szyłło, Krzysztof; Kulig, Andrzej; Romanowicz-Makowska, Hanna (Menopause Review/Przegląd Menopauzalny, 2004)
The enzymatic P 450 complex is responsible for synthesis and metabolism of estrogens and progesteron. A strong relationship between polymorphism in the CYP 450 complex and enzyme activity has been observed in many articles. This article is a summary of available data, described influence polymorphism CYP 450 gene on endometrial cancer and other hormone – dependent cancers.